Exploring decision-making prospective mathematics teacher in solving geometric proof problems - Masfingatin, Titin; Apriandi, Davi; Murtafiah, Wasilatul; Suprapto, Edy; Lusiana, Restu (Universitas Hamzanwadi, 2024)
Facing the current digital era, correct and accurate decisions are needed to deal with the problems. This research aimed to explore the decision-making abilities of prospective mathematics teacher students in solving geometric proof problems. This research was a qualitative descriptive study with research subjects 3 out of 32 students of the 2nd semester Mathematics Education study program. The research instrument is the researcher himself, who is assisted with geometric proof problem tests and interview guidelines. Data analysis was including reduction, presentation, and conclusion. The validity of the research data was tested using methods triangulation. The research results show that subjects with a proof ability of K2 can build and clarify geometric concepts/principles and can assess the reasonableness of ideas even though the subject feels unsure about their choice. Subjects with a proof ability of K3 can build and clarify geometric concept/principle ideas but cannot assess the reasonableness of proof ideas. Subjects with a proof ability of K4 can build ideas of geometric concepts/principles, can clarify even though they are incomplete, and cannot assess the reasonableness of proof ideas. Students need to be equipped with decision-making skills in solving proof problems as preparation to become mathematics teachers in the future.